Menganalisis Peran Gender, Tahun Akademik, dan Status Mahasiswa dalam Self-Efficacy Akademik di Kalangan Mahasiswa Muslim - Elia Firda Mufidah; Cindy Asli Pravesti; Fatimah Az Zahrah Binti Zolkeplai (Pamomong: Journal of Islamic Educational Counseling, 2025)
Academic self-efficacy refers to an individual’s belief in their capability to successfully execute academic tasks and is a critical determinant of academic achievement. This study investigates the influence of gender, academic year, and student status on students’ academic self-efficacy. Employing a quantitative correlational design, data were collected from 132 Muslim students enrolled in the Guidance and Counseling Program at Universitas PGRI Adi Buana Surabaya, using a validated self-efficacy scale (KMO-MSA = .82; α = .912). Correlational and regression analyses indicated no statistically significant relationships or effects of gender (p = .899), academic year (p = .151), or student status (p = .677) on academic self-efficacy. Collectively, these variables accounted for only 1.8% of the variance, implying the presence of other influential factors. This study contributes to the understanding of academic self-efficacy within an Islamic context and underscores the limited predictive power of demographic variables. Future research should examine psychological, motivational, and contextual factors—such as learning strategies, emotional states, and religious values. Additionally, longitudinal and mixed-methods approaches across multiple institutions are recommended to elucidate causal mechanisms and provide a more comprehensive understanding of the development of academic self-efficacy among Muslim students.